Criterios de inclusión social para la educación formal e informal, de las personas con movilidad reducida del municipio de Candelaria, Valle del Cauca. (2022)
The fact w as born when we found that at the city level, the context built for people with reduced mobility has become a physical barrier, which in some cases prevents freedom in many places, both public and private; Thus, one route to follow is to be able to break d own these architectural barriers that hinder social inclusion.